PEWARISAN MUSIK IRINGAN TARI GANDANG DI NAGARI PAUH IX KECAMATAN KURANJI KOTA PADANG - Deria Sepdwiko (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
This article aims to reveal and describe the Inheritance of Gandang Dance music in Nagari Pauh IX Kuranji Subdistrict, Padang City. This research type is qualitative research with descriptive method. The object of this research is Gandang dance music in Nagari Pauh IX Kecamatan Kuranji Kota Padang. Data were collected through literature study, observation, interview and documentation. Data analysis is done by referring to ethnography technique. The findings of research indicate that Gandang dance music is a traditional dance in Nagari Pauh IX Kuranji subdistrict of Padang City and grows and develops in pencak silat target area, traditional music and dance. which is located in Nagari Pauh IX, precisely in the area of Katapiang. In the development of Gandang dance music tradition has developed from the aspect of inheritance. At the beginning of Gandang dance music in Nagari Pauh IX, the inheritance system is more likely to be closed, that is through blood and kinship affinities. While the present when entering the 1975s, has developed a system of inheritance from a closed system through blood and kinship relationship to the open system through learning from teacher to pupil in pencak silat target.Keywords : Gandang Dance Music, Inheritance System and Nagari Pauh IX